ANALISIS PENERAPAN METODE FIFO PADA PENYIMPANAN BAHAN MAKANAN DI MAIN KITCHEN HOTEL MANADO TATELI RESORT & CONVENTION - Pangajow, Cindy Lestari; Wewengkang, Silvana; Sinolungan, Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the application of the First In, First Out (FIFO) method in food ingredient storage at the main kitchen of Manado Tateli Resort & Convention. The background of this research is the gap between the storage procedure that should be followed and its practice in the field, where during peak operations newly arrived ingredients are sometimes used before the older stock. A qualitative descriptive approach was applied, with data collected through direct observation, in-depth interviews with five kitchen informants (Executive Chef, Sous Chef, Chef de Partie, Commis, and Purchasing staff), and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that FIFO has become a core operating standard and runs at a consistency level of about eighty-five percent: incoming goods are inspected, weighed, washed, labeled, and stored by category, while older stock is issued first. The main obstacles do not lie in the system itself but in human resources and physical limitations, namely limited staff during high occupancy, last-minute event requests, restricted storage space, and inconsistent supplier labeling. The efforts undertaken include direct supervision by leaders, verbal and written warnings or training, re-arranging stock after busy service, coordinating with purchasing, and re-labeling supplier goods. The study concludes that a disciplined and consistent application of FIFO supports ingredient quality, controls food cost, and reduces food waste.